A combined path index for efficient processing of XML queries. (2018) - Dhanalekshmi, G.; Asawa, Krishna
In today's digitally connected world, diverse applications use data in various formats. The flexible nature of the XML has motivated applications in various fields like technical to financial to drift towards the XML representation. The emerging drift towards XML applications increased the number of documents exponentially over the web. Thus, unprecedented growth in the usage of XML documents on the web warrants research attention towards efficient methodologies to facilitate accelerated query processing of XML documents. This paper proposes a new indexing structure which combines terminal sibling nodes at the same level into a single path thereby reducing the search space while querying. The main advantage of this index is that it can process the branch (twig) queries efficiently with fewer lookups and decompositions in contrast with the existing approaches. The results also show that they are processed with equal or better performance compared to the existing ones.